379 Occupational exposure to trichloroethylene and risk of non-Hodgkin lymphoma and its major subtypes: a pooled interlymph analysis. (11th October 2013) - Cocco, P C; Vermeulen,; Flore,; Nonne,; Campagna,; Purdue,; Blair,; Monnereau,; Orsi,; Becker,; De Sanjosé,; Foretova,; et al.
Abstract : Objectives: To test the association between occupational exposure to trichloroethylene (TCE) and risk of non Hodgkin lymphoma (NHL), we conducted a pooled analysis of four international case-control studies. Methods: Studies were selected which included state-of-the art retrospective assessment of occupational exposure to TCE and histological information on lymphoma subtype. Overall, the pooled study population included 3788 NHL cases and 4279 controls. Summary indicators of exposure were harmonised across studies. We conducted unconditional logistic regression analysis to test the association between the harmonised TCE exposure estimates and NHL and its major subtypes, adjusting by age, gender, and study. Results: Among the total study population, risk of follicular lymphoma, but not NHL overall or other subtypes, increased by probability ( p = 0.02) and intensity level ( p = 0.04) of TCE exposure. When the analysis was restricted to subjects most likely exposed to TCE, risk of NHL overall ( p = 0.009), follicular lymphoma ( p = 0.04), and chronic lymphocytic leukaemia (CLL) ( p = 0.01) showed a linear increase by duration of exposure. No heterogeneity in NHL risk associated with high probability of exposure to TCE (all intensity levels combined) was detected. Conclusion: With due caution because of several limitations, our pooled analysis supports the hypothesis of an increased risk of NHL, and particularly of the follicular lymphoma and CLL subtypes, associated with occupational exposure to TCE.